Comparison of patient reported dry eye symptoms as evaluated by the ocular surface disease index and symptom assessment - Solani D. Mathebula; Percy R. Khosa; Mmathabo M. Maleswene (African Journal of Primary Health Care & Family Medicine)
Background: Dry eye disease (DED) is a growing public health problem because of excessive time spent on digital devices as a risk factor. The diagnosis of DED should not only be based on the objective clinical measures but also on symptoms reported by patients. Clinicians should not rely on establishing symptoms using open verbal questioning during the case history but should quantify patient symptoms using a validated questionnaire.